2021
DOI: 10.3390/ijms22189973
|View full text |Cite
|
Sign up to set email alerts
|

Functional Changes of T-Cell Subsets with Age and CMV Infection

Abstract: Cytomegalovirus (CMV) latent infection and aging contribute to alterations in the function and phenotype of the T-cell pool. We have demonstrated that CMV-seropositivity is associated with the expansion of polyfunctional CD57+ T-cells in young and middle-aged individuals in response to different stimuli. Here, we expand our results on the effects of age and CMV infection on T-cell functionality in a cohort of healthy middle-aged and older individuals stratified by CMV serostatus. Specifically, we studied the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 70 publications
1
32
1
Order By: Relevance
“…In our healthy cohorts of young and elderly donors (YHD and HD), we registered an age-associated increase in the proportion of senescent CD57 + cells in accordance with the data reported previously [ 52 ]. CMV-positive individuals demonstrated higher levels of CD57 + cells in CD56 − and CD56 + T cell subsets than CMV-negative donors from YHD and HD groups ( Figure 5 a and Figure 8 a).…”
Section: Discussionsupporting
confidence: 90%
“…In our healthy cohorts of young and elderly donors (YHD and HD), we registered an age-associated increase in the proportion of senescent CD57 + cells in accordance with the data reported previously [ 52 ]. CMV-positive individuals demonstrated higher levels of CD57 + cells in CD56 − and CD56 + T cell subsets than CMV-negative donors from YHD and HD groups ( Figure 5 a and Figure 8 a).…”
Section: Discussionsupporting
confidence: 90%
“…Consequently, chronic or latent CMV infection can eventually lead to the inflation of terminally differentiated memory CD8 + T cells and immune dysfunction in old adults [6][7][8]. Recent study of CMV infection in healthy young and middleaged adults showed increased CD57 expression in T cells [9], but it is unknown whether such increase only in CMV-specific or in non CMV-specific T cells. Overall, the molecular mechanisms of CMV infection caused changes of CMV-specific CD8 + T cells in healthy young and middle-aged adults is not fully examined.…”
Section: Introductionmentioning
confidence: 99%
“…These studies suggest that CMV reactivation may have the potential to serve as a sepsis-related proinflammatory factor and immune activation indicator, and demonstrate that bone marrow-derived cells are activated by CMV infection and differentiated into specific functional effector cells. A recent study by Hassouneh et al 38 indicated that CMV infection leads to functional changes in T-cell subtypes. Therefore, it is reasonable to assume that CMV infection may impair cytotoxic lymphocyte response to CMV, which in turn contributes to poor Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Hassouneh et al . 38 indicated that CMV infection leads to functional changes in T‐cell subtypes. Therefore, it is reasonable to assume that CMV infection may impair cytotoxic lymphocyte response to CMV, which in turn contributes to poor prognosis in patients with sepsis.…”
Section: Discussionmentioning
confidence: 99%